Outcomes of Chronic Hepatitis C Therapy in Patients Treated in Community Versus Academic Centres in Canada: Final Results of APPROACH (A Prospective Study of Peginterferon alfa-2a and Ribavirin at Academic and Community Centres in Canada). (2011) - Myers, Robert P; Cooper, Curtis; Sherman, Morris; Lalonde, Richard; Witt-Sullivan, Helga; Elkashab, Magdy; Harris, Paul; Balshaw, Rob; Usaty, Christopher; Marotta, Paul J
Abstract : BACKGROUND: In patients chronically infected with the hepatitis C virus (HCV), it is not established whether viral outcomes or health-related quality of life (HRQoL) differ between individuals treated at academic or community centres. METHODS: In the present observational study, adults with chronic HCV were treated with peginterferon alfa-2a 180 μg/week plus ribavirin at 45 Canadian centres (16 academic, 29 community). The primary efficacy end point was sustained virological response (SVR). Other outcome measures included HRQoL (assessed using the 36-item Short-Form Health Survey), heath resource use, and workplace productivity and absences within a 60-day interval. RESULTS: In treatment-naive patients infected with HCV genotype 1, significantly higher SVR rates were achieved in those treated at academic (n=54) compared with community (n=125) centres (52% versus 32% [P=0.01]), although rates of dosage reduction and treatment discontinuation were similar across settings. SVR rates among patients infected with genotype 2/3 were similar between academic (n=59) and community (n=100) centres (64% versus 67% [P=0.73]). Following antiviral therapy, patients with genotype 1 who achieved an SVR (n=67) had significantly higher mean scores on the physical (P=0.005) and mental components of the 36-item Short-Form Health Survey (P=0.043) compared with those without an SVR (n=111). In contrast, HRQoL scores were similar in HCV genotype 2/3 patients with and without an SVR. There were no differences in workplace productivity or absences between patients with and without an SVR. The most frequently used health care resources by all patients were visits and phone calls to hepatitis nurses, and general practice or walk-in clinics. CONCLUSION: Patients infected with HCV genotype 1 achieved higher SVR rates when treated at academic rather than community centres in Canada. The reasons for this difference require additional investigation.